Call for Papers: Captive Minds. Norms, Normativities and the Forms of Tragic Protest in Literature and Cultural Practice - Editors, RIAS (Review of International American Studies, 2017)
Call for papers for the 23rd International Conference of the Institute of English Cultures and Literatures University of Silesia in Katowice, September 20–23rd, 2018, Szczyrk, Poland